2005
DOI: 10.1007/s00277-005-1020-x
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in serum IL-6 and VEGF levels predict clinical outcome following first-line therapy in aggressive non-Hodgkin’s lymphoma

Abstract: Inflammatory cytokines play important roles in the pathogenesis of lymphomas and may reflect underlying biological processes including tumour-host interactions with prognostic information that is not afforded by conventional clinical parameters. Several lines of evidence suggest that serum levels of interleukin (IL)-6 and vascular endothelial growth factor (VEGF) are independent indicators of long-term outcome in non-Hodgkin's lymphoma (NHL), but the clinical impact of early serial monitoring of these cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
3
37
1
Order By: Relevance
“…Serum VEGF levels are at best an imperfect marker for VEGF levels within the lymphoma itself but are readily obtained; in a study of 64 patients with aggressive non-Hodgkin's lymphoma (61% DLBCL), early response over the first 3 weeks of treatment correlated with drops in serum VEGF (and IL-6). 25 Although no data exist on the effect of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) on VEGF or its receptors in DLBCL, evidence for downregulation of VEGF mRNA expression by these agents exists in several other model systems. [26][27][28][29][30][31] A model of the potential impact of anthracycline (doxorubicin) administration is presented in Figure 5c.…”
Section: Discussionmentioning
confidence: 99%
“…Serum VEGF levels are at best an imperfect marker for VEGF levels within the lymphoma itself but are readily obtained; in a study of 64 patients with aggressive non-Hodgkin's lymphoma (61% DLBCL), early response over the first 3 weeks of treatment correlated with drops in serum VEGF (and IL-6). 25 Although no data exist on the effect of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) on VEGF or its receptors in DLBCL, evidence for downregulation of VEGF mRNA expression by these agents exists in several other model systems. [26][27][28][29][30][31] A model of the potential impact of anthracycline (doxorubicin) administration is presented in Figure 5c.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis, including descriptive methods, was performed using the SPSS software V. 10.0 for Windows. The Pearson x 2 test and the Spearman rank correlation coefficient were applied where appropriate to demonstrate correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently suggested an important role in hematologic malignancies as well (Smolej et al 2005;Ribas et al 2004;Pedersen et al 2005;Singhal et al 1999;Dmoszynska et al 2005). There is evidence that angiogenesis, as measured by an increase in angiogenic factors and an increase in microvessel density (MVD), may be important in lymphomagenesis.…”
Section: Introductionmentioning
confidence: 95%